A method to standardize quantification of left atrial scar from delayed-enhancement MR images - Karim, Rashed; Arujuna, Aruna; Housden, Richard James; Gill, Jaspal; Cliffe, Hannah; Matharu, Kavir; Gill, Jaswinder; Rindaldi, Christopher Aldo; O'Neill, Mark; Rueckert, Daniel; Razavi, Reza; Schaeffter, Tobias; et al. (IEEE Journal of Translational Engineering in Health and Medicine, 2014)
Delayed-enhancement magnetic resonance imaging (DE-MRI) is an effective technique for detecting left atrial (LA) fibrosis both pre and postradiofrequency ablation for the treatment of atrial fibrillation. Fixed thresholding models are frequently utilized clinically to segment and quantify scar in DE-MRI due to their simplicity. These methods fail to provide a standardized quantification due to interobserver variability. Quantification of scar can be used as an endpoint in clinical studies and therefore standardization is important. In this paper, we propose a segmentation algorithm for LA fibrosis quantification and investigate its performance. The algorithm was validated using numerical phantoms and 15 clinical data sets from patients undergoing LA ablation. We demonstrate that the approach produces good concordance with expert manual delineations. The method offers a standardized quantification technique for evaluation and interpretation of DE-MRI scans.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adaptation models; Biomedical imaging; Blood; Image segmentation; Magnetic resonance imaging; Myocardium; Training